Role of Rubber Stiffness and Surface Roughness in the Tribological Performance on Ice. Issue 2 (4th March 2018) - Isitman, Nihat A.; Kriston, András; Fülöp, Tibor
ABSTRACT: The aim of this work is to investigate the effect of slider surface roughness and stiffness on the friction between rubber compounds and ice surfaces in order to provide insight into rubber–ice friction generation mechanisms. For this purpose, rubber compounds were designed to have different levels of macroscopic roughness and cured stiffness by modifying the filler system and plasticizer loading. In order to accurately evaluate the effects of surface and bulk rubber property on ice friction, linear friction tests were performed on laboratory ice with varied frictional heat buildup by modifying the friction test protocol. The results showed that the friction force was in general increased through the ploughing effect of a rough rubber block sliding on smooth ice. The increase in friction by ploughing was more pronounced when the contacting rubber block had sufficiently low stiffness and when the accumulation of frictional heat on ice was sufficiently high. It was also evidenced that a sufficiently hard rubber with test conditions leading to low heat buildup on ice could nevertheless lead to an opposite influence of roughness on rubber–ice friction; that is, lower friction force with a slider with a higher roughness.